Identification of Special Talents in Swimming Pool Blitar District Towards PORPROV 2021 East Java - Wing Prasetya Kurniawan; Reo Prasetiyo Herpandika; Rendhitya Prima Putra; Mokhammad Firdaus; Septyaning Lusianti (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2020)
This special talent identification activity was aimed at Blitar Regency swimming athletes who were registered in the Blitar PRSI Pengcab District with the intention that netted talented athletes to represent Blitar Regency in the PORPROV 2021 event. The method of identifying special swimming sport talent was using the Anthropometry test and the Biomotor swimming component as many as 32 athletes. From the test results, seven male and seven female athletes were selected to be included in the Blitar Regency swimming team. This kind of activity should be carried out routinely, monitoring physical abilities should be carried out every six months and identifying special swimming sports talent is also aimed at junior athletes in the hope that the regeneration of swimming athletes in the Blitar Regency continues.